2005
DOI: 10.1207/s15328015tlm1704_10
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Clinical Medicine: An Interclerkship Program

Abstract: The interclerkship format is a viable approach for incorporating orphan topics into the clinical curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Several schools built on existing, successful CAM-related centers or programs (University of California-San Francisco, University of North Carolina, University of Michigan, and University of Minnesota). (18)(19)(20) Although the total of students enrolled in the study may not have been convincingly representative (46% of the total of students that concluded the discipline - Table 1), and this would be a loss for this study, considering the universe of students that concluded the elective discipline of acupuncture, there is some interesting information we can obtain from the study.…”
Section: Discussionmentioning
confidence: 99%
“…Several schools built on existing, successful CAM-related centers or programs (University of California-San Francisco, University of North Carolina, University of Michigan, and University of Minnesota). (18)(19)(20) Although the total of students enrolled in the study may not have been convincingly representative (46% of the total of students that concluded the discipline - Table 1), and this would be a loss for this study, considering the universe of students that concluded the elective discipline of acupuncture, there is some interesting information we can obtain from the study.…”
Section: Discussionmentioning
confidence: 99%
“…It can be direct observation or skill-based training where the learning takes place by reflecting on own experiences of dealing with clients. 36 Along similar lines, a systematic review had suggested that training can improve healthcare professionals’ sensitivity, empathy, and compassion by encouraging them to be able to recognize clients’ emotions and be supportive toward them. 37 Considering clients’ perspective and not rushing through the process of history taking. The inclusion of compassion- and kindness-based training in the mainstream curriculum is proposed.…”
Section: Toward a Compassionate Mental Healthcarementioning
confidence: 99%
“…It can be direct observation or skill-based training where the learning takes place by reflecting on own experiences of dealing with clients. 36 Along similar lines, a systematic review had suggested that training can improve healthcare professionals' sensitivity, empathy, and compassion by encouraging them to be able to recognize clients' emotions and be supportive toward them. 37 • Considering clients' perspective and not rushing through the process of history taking.…”
Section: Toward a Compassionate Mental Healthcarementioning
confidence: 99%
“…Similarly, the University of California San Francisco Medical School has implemented three one-week intersessions on evidence-based medicine, ethics, health systems, advances in science affecting clinical practice, and professional development (Fenton et al 2002). Finally, Creighton University School of Medicine recently reported on a series of two-day interclerkships addressing evidence-based medicine, sexuality in clinical medicine, professionalism, cultural sensitivity/awareness, complementary and alternative medicine, bioterrorism, and clinical ethics (Sakowski et al 2005). Earlier UCLA introduced a longitudinal, multidisciplinary third-year course that included a small-group component in which underrepresented topics such as ethics, domestic violence and nutrition were addressed through the use of standardized patients (Slavin et al 1995).…”
Section: Introductionmentioning
confidence: 99%